Strategies to Competitiveness of Logistics Business in Luangprabang City - Phommachanh, Khamphout; YANGSANSAY , Chahue; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
International study of strategies to create competitive advantages of transport business operators in Luang Prabang capital which includes 3 objectives: study the competitive conditions and business operations of transport business operators in Luang Prabang capital, strategies to create competitive advantages of transport business operators in Luang Prabang capital and study the factors that affect the strategies of transport business operators in Luang Prabang capital. Analysis of various statistical data with the SPSS program by bringing the data collected from the actual questionnaire to a code as specified for the closed-ended questions, and then save it in the program to analyze the statistical data such as frequency values, percentage values, average values (Mean), standard deviation values (Std. Deviation), correlation coefficient values, statistical significance values, the results of the study are as follows: In terms of information on the external factors of the competition of the transport business in Luang Prabang, it was found that: overall, the transport business operators in the capital Prabang give importance to the external factors of competition. Overall, at a very effective level, when considering each aspect, it is found that: the transport business operators in the Prabang capital give importance to the factors of the external competition. They give importance to the economic factors as the first at the highest level, followed by the political factors and the threat from substitute products at the most levels, and the next level is the competitive factors of the same type of business at the highest level. In terms of information on the internal competitive factors of the transport business in Luang Prabang, it was found that: Overall, the transport business operators in the Prabang capital give importance to the internal competitive factors, as a whole, to a very effective level. When considering each aspect, it is found that: the transport business operators in the Prabang capital give importance to the internal competitive factors, giving importance to the financial factors first in many levels, followed by the research and development factors in many levels, and the administrative factors in many levels. In terms of information on the factors of competition in terms of characteristics of transport business operators in Luang Prabang, it was found that: Overall, transport business operators in Prabang capital give importance to the factors of competition in terms of the characteristics of operators, as a whole, at a very effective level. When considering each aspect, it is found that: transport business operators in the capital of Prabang give importance to the factors of competition in terms of the characteristics of operators. They give importance to the self-esteem factor in the first place at the highest level.